Involvement of the intracellular β-glucosidase BGL1B from Aspergillus niger in the regulation of lignocellulose-degrading enzymes’ synthesis - Zhen Zhang; Hua Li; Feiyu Dong; Hui Lin; Yanan Li; Kun Cheng; Hongge Chen (Biotechnology for Biofuels and Bioproducts)
Abstract Background Aspergillus niger is an important lignocellulose-degrading enzyme-producing strain. Multiple regulatory factors regulate the synthesis of lignocellulose-degrading enzymes in A. niger. We previously found that A. niger possessed an intracellular β-glucosidase BGL1B, and the intracellular localization of BGL1B and its active transglycosylation action prompted us to explore whether BGL1B was involved in the regulation of the synthesis of lignocellulose-degrading enzymes in A. niger. Results In this study, by investigating the production of lignocellulose-degrading enzymes of bgl1B knockout strain (Δbgl1B) and overexpression strain (OE::bgl1B), it was found that BGL1B exhibited a repressive role on the expression of lignocellulose-degrading enzyme genes through carbon catabolite repression (CCR) way. On the other hand, BGL1B’s transglycosylation products sophorose and laminaribiose were proved to be able to induce the expression of lignocellulose-degrading enzyme genes, which explained why OE::bgl1B showed the same enhanced enzyme activity and gene expression as Δbgl1B strain compared to the starting strain (WT). Conclusions The present study demonstrates that BGL1B plays dual regulatory roles in the regulation of the synthesis of lignocellulose-degrading enzymes in A. niger: the repressive role caused by BGL1B’s hydrolysis product glucose and the induction role caused by BGL1B’s transglycosylation products sophorose and laminaribiose. This study broadens the understanding of the regulatory network of the synthesis of lignocellulose-degrading enzymes in A. niger. Also, it provides a strategy to create an engineered strain with high production of lignocellulose-degrading enzymes.